Safety of Radial vs. Femoral Artery Access in Coronary Angiography - Kabir, CM Shaheen; Haq, M Maksumul; Khan, Saidur Rahman; Chowdhury, Mashhud Zia; Ali, Mohammad Liaquat; Karim, Md Rezaul (Bangladesh Heart Journal, 2016)
Background: To evaluate the safety of radial versus femoral artery approach in routine coronary angiography (CAG) practice. Methods: We retrospectively evaluated consecutive patients in Ibrahim Cardiac Hospital & Research Institute, a tertiary care centre, who underwent diagnostic CAG over a period of 12 months. Procedure duration was calculated as time from initiation of local anesthesia to completion of the procedure. Contrast volume and fluoroscopy time were recorded. Results: 3346 patients who underwent a diagnostic CAG were included in this study. The radial approach was used in 3030 patients (90.5%) and the femoral approach in 316 patients (9.5%). As the radial group was disproportionately large compared to femoral group the size of the radial group was reduced to 1010 using a systematic sampling procedure, where every 3rd patient of radial group was chosen.Fluoroscopy and procedural times were not significantly different (3.41±1.14 vs. 3.85±1.43 min, p=0.314 & 11.87±4.61 vs. 13.74±6.33 min, p=0.180, respectively) comparing the radial and femoral approaches. While contrast utilization during the procedure was significantly lower in the radial than the femoral approach (57.60±22.42 vs. 69.52±24.30 mL respectively, p=0.030). Conclusion: Transradial coronary angiography can be safely performed as the transfemoral approach. Bangladesh Heart Journal 2015; 30(2) : 68-73